Country score tool to assess readiness and guide evidence generation of immunization programs in aging adults in Europe - Pham, Thi Hao; Beck, Ekkehard; Postma, Maarten J.; Németh, Bertalan; Ágh, Tamás; de Waure, Chiara; Salisbury, David M.; Nutma, Nynke; van der Schans, Jurjen (Frontiers in Public Health, 2023)
OBJECTIVES Delaying of policies for immunization of ageing adults, low vaccine uptake, and the lack of supportive evidence at the national level could diminish the value in health and economics of such programs. This study aims to develop a “country score tool” to assess readiness and to facilitate evidence generation for ageing adult immunization programs in Europe, and examine the comprehensiveness, relevance, acceptability, and feasibility of the tool. METHODS The tool was developed in two phases. First, a modified Delphi process was used to construct the tool. The process included a literature review, stakeholder consultations, and a three-round Delphi study. The Delphi panel included researchers, supra-national and national decision-makers of immunization programs recruited from five countries, using snowball sampling method. The consensus was predefined at the agreement rate of 70%. Pilot testing of the tool was conducted in the Netherlands, Germany, Serbia, and Hungary involving researchers in the field of health technology assessment. After assessing the countries’ readiness, researchers evaluated four features, namely comprehensiveness, relevance, acceptability, and feasibility of the tool via an online survey that included 5-scale Likert questions. The percentages of affirmative answers including “agree” and “totally agree” choices were presented. RESULTS The review identified 16 tools and frameworks that formed the first version of our tool with 14 items. Eight experts were involved in the Delphi panel. Through three Delphi rounds, four items were added, one was dropped, and all others were amended. The consensus was achieved on the tool with 17 items divided into decision-making and implementation parts. Each item has a guiding question, corresponding to explanations and rationales to inform assessment with readiness scores. Eight researchers completed the pilot testing. The tool was rated as comprehensive (75%), relevant (100%), acceptable (75%), and feasible (88%) by participants. CONCLUSION Through a thorough and transparent process, a country score tool was developed helping to identify strengths, weaknesses, and evidential requirements for decision-making and implementation of immunization programs of ageing adults. The tool is relevant for different European contexts and shows good comprehensiveness, acceptability, and feasibility.